Correlation of foaming properties of plant-based beverages with physicochemical composition - A. V. Tarasov; N. V. Zavorokhina; O. V. Chugunova; A. V. Vyatkin (Пищевые системы, 2025)
Demand for unique cappuccino and latte flavors has led to research into the foaming properties of plant-based beverages, among which the greatest potential for use in catering organizations are drinks intended for professional use by baristas. This work investigated the foaming and physicochemical properties of plant-based beverages and cow’s milk for cappuccino labeled “Barista”. Samples were foamed at temperatures simulating the consumption of hot and cold coffee beverages and evaluated for foaming capacity (FC) and foam stability (FS). After steam treatment at 65 °C, agitation at 65 °C and 10 °C, the plant-based drinks showed FC in the ranges of 93–202 %, 15–262 % and 0–196 %, respectively, whereas under similar conditions, the FC of milk was 197, 258 and 200 %. The analyzed coconut drink foamed at 65 °C but did not froth at 10 °C, presumably due to its thick consistency and increased viscosity. In terms of foam quantity and stability, all plant-based drinks were viable alternatives to milk for cappuccino in the case of steam injection, but not in the case of mechanical agitation. Foaming properties of plant-based drinks were not correlated with most nutrients and the studied physicochemical parameters (pH, density, total solids and total polyphenol content). However, a negative correlation of fats with FC of plant-based drinks was found when stirred (p < 0.05), a similar trend was observed for steam injection (p = 0.08). The lack of correlation with proteins highlights the difficulty of controlling foam characteristics in professional plant-based beverages and may be due to synergistic effects between proteins and stabilizers in foaming. Future works should encourage the study of the effects of gums, carrageenans and other stabilizers on foaming.